Digitally Integrated Project-Based Contextual Physics Resources to Enhance Students' Critical Thinking Skills to Support SDG-4 - Khaeruddin; Wahyuni, Andi Sri Astika; Kijkuakul, Sirinapa (Universitas Negeri Semarang, 2025)
This study aims to determine the effectiveness and ease of using digitally integrated project-based contextual physics resources in strengthening students' critical thinking skills, to support the achievement of Sustainable Development Goal 4 (SDG-4). The research method used was a quasi-experimental one-group pretest-posttest design involving senior high school students in South Sulawesi, Indonesia. Data analysis was conducted using descriptive and inferential statistical tests. The results showed that digitally integrated project-based contextual physics resources were effective in improving students' critical thinking skills with a significance level of <0.05. The findings revealed a substantial improvement in students' critical thinking skills, indicated by an increase in the mean score from 28.23 (pre-test) to 70.07 (post-test). In addition, the contextual physics resources were also considered very easy to use by teachers and students in the physics learning process, with an average practicality score of >80%, categorized as